2010
DOI: 10.4317/medoral.15.e886
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic signs associated with inferior alveolar nerve damage following lower third molar extraction

Abstract: The aim was to carry out a literature review of preoperative radiographic signs in orthopantomography (OPG) and computed tomography (CT) related with the risk of inferior alveolar nerve damage during the surgical extraction of lower third molar (LTM). A search was made on PubMed for literature published between the years 2000 and 2009. In the reviewed literature, radiographic signs in the OPG that indicate a relationship between the LTM and the inferior alveolar canal are considered a risk factor for nerve dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 15 publications
1
24
0
1
Order By: Relevance
“…Although panoramic images cannot provide three-dimensional information, numerous clinical studies [ 2 , 5 , 7 , 11 -13, 17 ] have been performed to determine panoramic findings suggestive of inferior alveolar nerve exposure or postoperative dysesthesia. In addition, many studies reported the panoramic findings that associated direct contact between inferior alveolar nerve and impacted third molar on computed tomography or cone-beam CT images [ 8 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although panoramic images cannot provide three-dimensional information, numerous clinical studies [ 2 , 5 , 7 , 11 -13, 17 ] have been performed to determine panoramic findings suggestive of inferior alveolar nerve exposure or postoperative dysesthesia. In addition, many studies reported the panoramic findings that associated direct contact between inferior alveolar nerve and impacted third molar on computed tomography or cone-beam CT images [ 8 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to evaluate the topographic relationship between the mandibular canal and impacted third molar preoperatively. There were reports [ 6 , 7 , 9 , 11 ] that showed the following 4 panoramic features were significantly associated with inferior alveolar nerve exposure following third molar extraction: interruption of mandibular canal, darkening of third molar root, diversion of mandibular canal and narrowing of third molar root. In addition, many studies reported that the interruption of mandibular canal was the most found panoramic feature that associated with direct contact between the two structures, which could be the risk of nerve injury and paraesthesia [ 2 , 6 , 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, it has been shown that the darkening of the root can even present as the evidence of thinning of the lingual cortical plate without root grooves 12. The interruption of the cortical line of the canal on panoramic radiograph was related to the absence of cortical bone on computed tomography (CT) image 13. It has been reported that the absence of the cortical bone of the canal was closely related to the exposure of IAN 14…”
Section: Introductionmentioning
confidence: 99%
“…In general, the most common problems after removing the wisdom tooth are complications such as pain, swelling, trismus, and the anesthetic of the lingual nerve, infection, etc. which occur due to the trauma to the tissue and the inflammation caused by it (3,4). Inflammation is the natural defense mechanism of the body to damage or cell death, which is characterized by redness, warmth, pain and swelling in the area (5).…”
Section: Introductionmentioning
confidence: 99%